Characteristics and functions of volatile organic compounds in the tripartite symbiotic system of Gastrodia elata-Armillaria gallica-Rahnella aceris HPDA25 - Ying Zhang; Tianrui Liu; Tiegui Nan; Zhongyi Hua; Yuyang Zhao; Yuan Yuan (Plant Signaling & Behavior)
Tripartite interactions among plants, fungi, and bacteria are critical for maintaining plant growth and fitness, and volatile organic compounds (VOCs) play a significant role in these interactions. However, the functions of VOCs within the niche of mycoheterotrophic plants, which represent unique types of interactions, remain poorly understood. Gastrodia elata, a mycoheterotrophic orchid species, forms a symbiotic relationship with specific Armillaria species, serving as a model system to investigate this intriguing issue. Rahnella aceris HPDA25 is a plant growth-promoting bacteria isolated from G. elata, which has been found to facilitate the establishment of G. elata-Armillaria symbiosis. In this study, using the tripartite symbiotic system of G. elata-Armillaria gallica-R. aceris HPDA25, we investigate the role of VOCs in the interaction among mycoheterotrophic plants, fungi, and bacteria. Our results showed that 33 VOCs of HPDA25-inducible symbiotic G. elata elevated compared to non-symbiotic G. elata, indicating that VOCs indeed play a role in the symbiotic process. Among these, 21 VOCs were accessible, and six active VOCs showed complete growth inhibition activities against A. gallica, while R. aceris HPDA25 had no significant effect. In addition, three key genes of G. elata have been identified that may contribute to the increased concentration of six active VOCs. These results revealed for the first time the VOCs profile of G. elata and demonstrated its regulatory role in the tripartite symbiotic system involving G. elata, Armillaria, and bacteria.